PENGEMBANGAN MODEL SEARCHING INFORMATION SKILL DALAM PEMBELAJARAN IPS - Bahar Triono; Darsono Darsono; Iskandar Syah (Jurnal Studi Sosial / Journal of Social Studies, 2013)
This research aims to develop learning model of Searching Information Skill (SIS), to know the effectivitiveness of Searching Information Skill (SIS) model.  This developing research used Borg and Gall model with five steps or phases. The result of this research showed that; In developing learning model of Searching Information Skill, by adding learning steps in the beginning activity by performing learning video or printed and electronic media as a source of learning besides sources appeared in Learning Implementation Planning (RPP), through material expertise validation, the design expert of Social Studies teacher scoring learning as the user and the students. The model of Searching Information Skill was effectively used in Social Studies learning, and also highest score increase from 82 to 92. Besides, there was also an increase on pretest score from the highest 44 to 92 or an increase of 85%  of  students  who completed on Basic Competency of Understanding Social Institutions.Tujuan penelitian ini adalah mengembangkan model pembelajaran Searching Information Skill (SIS), mengetahui efektifitas model Searching Information Skill (SIS). Penelitian pengembangan ini menggunakan model Borg and Gall dengan lima langkah atau tahapan. Hasil penelitian ini menunjukkan bahwa; Dalam mengembangkan Model Pembelajaran Searching Information Skill, dengan menambahkan langkah-langkah pembelajaran pada kegiatan awal yaitu dengan penayangan video pembelajaran atau media cetak dan elektronik sebagai sumber belajar selain nara sumber yang tertuang dalam RPP, dengan melalui validasi ahli materi, ahli desain pembelajaran penilaian guru IPS sebagai pengguna dan siswa. Model pembelajaran Searching Information Skill efektif digunakan dalam pembelajaran IPS, serta peningkatan nilai tertinggi dari 82 menjadi 92. Selain itu juga ada peningkatan nilai pretes dari tertinggi 44 menjadi 92 atau peningkatan sebesar 85% siswa yang tuntas pada KD Memahami Pranata Sosial.Kata kunci: pembelajaran IPS, pengembangan model, searching information skill